Chaperones as Suppressors of Protein Misfolded Oligomer Toxicity - Mannini, Benedetta; Chiti, Fabrizio (Frontiers in Molecular Neuroscience, 2017)
Chaperones have long been recognized to play well defined functions such as to (i) assist protein folding and promote formation and maintenance of multisubunit complexes, (ii) mediate protein degradation, (iii) inhibit protein aggregation and (iv) promote disassembly of undesired aberrant protein aggregates. In addition to these well-established functions, it is increasingly clear that chaperones can also interact with aberrant protein aggregates, such as pre-fibrillar oligomers and fibrils, and inhibit their toxicity commonly associated with neurodegenerative diseases without promoting their disassembly. In particular, the evidence collected so far in different labs, exploiting different experimental approaches and using different chaperones and client aggregated proteins, indicates the existence of two distinct mechanisms of action mediated by the chaperones to neutralise the toxicity of aberrant proteins oligomers: (i) direct binding of the chaperones to the hydrophobic patches exposed on the oligomer/fibril surface, with resulting shielding or masking of the moieties responsible for the aberrant interactions with cellular targets; (ii) chaperone-mediated conversion of aberrant protein aggregates into large and more innocuous species, resulting in a decrease of their surface-to-volume ratio and diffusibility and in deposits more easily manageable by clearance mechanisms, such as autophagy. In this review we will describe the in vitro and in vivo evidence supporting both mechanisms and how this results in a suppression of the detrimental effects caused by protein misfolded aggregates.